PERAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP RETENSI ANGGOTA: MEDIASI PROSES PEMURIDAN DALAM ORGANISASI KEAGAMAAN - Budi Harwanto (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study asks how transformational leadership shapes member retention in religious organizations, treating disciple making as the pathway that carries much of that influence. The motivation lies in a contradiction running through the literature: some studies tie transformational leadership to commitment and retention, while others find the effect weak or absent. A cross-sectional survey of 525 members of the Seventh-day Adventist Church in Eastern Indonesia was used to test the question. Transformational leadership was captured with a 20-item MLQ-informed scale, disciple making with 31 items, and member retention with 13 items, and the data were examined through Pearson correlation, stepwise regression, and structural equation modeling. Every dimension of transformational leadership related positively to retention. Inspirational motivation and intellectual stimulation stood out as the strongest predictors in the regression. The structural model traced two routes at once which is a direct effect on retention and an indirect effect running through disciple making that suggesting that transformational leadership keeps members chiefly when it sets calling, integrating, equipping, and involving in motion. The article extends transformational leadership theory into religious settings and points church leaders toward a discipleship-grounded practice rather than one that is merely charismatic or administrative. Keywords: transformational leadership; member retention; disciple making; religious organizations; structural equation modeling   Abstrak: Studi ini menguji bagaimana kepemimpinan transformasional memengaruhi retensi anggota di organisasi keagamaan, dengan proses pemuridan ditempatkan sebagai jalur mediasi. Persoalannya berangkat dari bukti empiris yang saling bertentangan. Sejumlah penelitian mengaitkan kepemimpinan transformasional dengan komitmen dan retensi, tetapi sebagian lain melaporkan efek yang lemah, bahkan tidak signifikan. Untuk menjawab ketegangan itu, survei potong lintang dilakukan terhadap 525 anggota Gereja Masehi Advent Hari Ketujuh di Indonesia Timur. Kepemimpinan transformasional diukur memakai 20 item yang diadaptasi dari Multifactor Leadership Questionnaire, proses pemuridan 31 item, dan retensi anggota 13 item. Data diolah melalui korelasi Pearson, regresi bertahap, dan structural equation modeling. Hasilnya konsisten: keempat dimensi kepemimpinan transformasional berkorelasi positif dengan retensi. Dalam regresi, inspirational motivation dan intellectual stimulation muncul sebagai prediktor terkuat. Model struktural memperlihatkan dua jalur sekaligus yaitu pengaruh langsung kepemimpinan terhadap retensi, dan pengaruh tidak langsung yang mengalir lewat proses pemuridan. Pola ini menyiratkan satu hal pokok: kepemimpinan transformasional menahan anggota untuk tetap tinggal justru ketika ia menggerakkan proses calling, integrating, equipping, dan involving. Artikel ini memperkaya teori kepemimpinan transformasional pada ranah organisasi keagamaan sekaligus menawarkan arahan praktis bagi gereja untuk membangun kepemimpinan yang berpijak pada pemuridan, bukan semata karisma atau kelihaian administratif. Kata kunci: kepemimpinan transformasional; retensi anggota; proses pemuridan; organisasi keagamaan; structural equation modeling